2013
DOI: 10.1164/rccm.201302-0295oc
|View full text |Cite
|
Sign up to set email alerts
|

Innate Type 2 Immunity Is Associated with Eosinophilic Pleural Effusion in Primary Spontaneous Pneumothorax

Abstract: Our results indicate that innate immune responses characterized by the production of IL-33, TSLP, and IL-5 are associated with the development of EPE in PSP by an ILC2-dependent and Th2-independent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 49 publications
0
30
0
1
Order By: Relevance
“…A recent study in patients with eosinophilic pleural effusion (EPE) associated with primary spontaneous pneumothorax (PSP) reported elevated expression of TSLP and IL-33 in the pleural fluid along with elevat-ed IL-5, eotaxin-3, and enhanced ILC2 responses (Kwon et al 2013). This study provokes the hypothesis that ILC2s may be the key driver of eosinophilia in the context of EPE and PSP.…”
Section: Ilc2s and Other Lung Diseasesmentioning
confidence: 80%
“…A recent study in patients with eosinophilic pleural effusion (EPE) associated with primary spontaneous pneumothorax (PSP) reported elevated expression of TSLP and IL-33 in the pleural fluid along with elevat-ed IL-5, eotaxin-3, and enhanced ILC2 responses (Kwon et al 2013). This study provokes the hypothesis that ILC2s may be the key driver of eosinophilia in the context of EPE and PSP.…”
Section: Ilc2s and Other Lung Diseasesmentioning
confidence: 80%
“…34 Enhanced accumulations of ILC2s have been reported at sites of eosinophilic inflammation, including nasal polyps and sinus mucosa in patients with chronic rhinosinusitis, skin lesions in patients with atopic dermatitis, and pleural effusions from patients with spontaneous pneumothorax. [35][36][37] Recent studies have reported that ILC2s, with a greater capacity to produce IL-5 and IL-13 on stimulation with epithelium-derived cytokines ex vivo, are found in the blood of allergic asthmatic patients compared with healthy control subjects. 38 In addition, increased numbers of ILC2s are found in the bronchoalveolar lavage fluid of patients with severe asthma compared with those in disease-matched control subjects.…”
Section: Abbreviations Usedmentioning
confidence: 99%
“…2932 Here, to extend this investigation and to examine whether innate type 2 immune response and/or ILC2s can be used as a biomarker of human diseases, we performed a prospective study. We addressed two specific questions: First, because blood specimens are more widely available than tissue specimens in clinical studies, we evaluated whether the innate type 2 response can be observed and whether ILC2s can be identified in peripheral blood.…”
Section: Introductionmentioning
confidence: 99%